Peterson's summer fun Travel & international programs - Peterson's (Firm) (Princeton, N.J Peterson's, 1999)
Includes profiles of selected camps and an alphabetical directory listing
American Corner
Latest issue consulted: 2001
First issue lacks designation
1
Keywords: Camps -- Directories; Outdoor recreation for children -- Directories; Summer schools -- Directories; Vacation schools -- Directories; Youth -- Recreation -- Directories